Optochemically Responsive 2D Nanosheets of a 3D Metal-Organic Framework Material - Chaudhari, Abhijeet K (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2017 The Authors. Published by WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.